2013
DOI: 10.1155/2013/742510
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Professionals’ Views on Managing Fibromyalgia

Abstract: The present study contributes to a better understanding regarding why current management of fibromyalgia is neither effective nor satisfactory. It also provides insight into how health professionals can support fibromyalgia patients to achieve beneficial results. Health care services should offer greater support for these patients in the form of specific resources such as fibromyalgia clinics and health professionals with increased awareness of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 58 publications
4
95
0
2
Order By: Relevance
“…In diseases such as fibromyalgia, the psychosocial aspects of medical management become more essential, which may be due in part to providers’ lack of training and knowledge in effective therapies that address these challenges [36]. Indeed, these patients expect more moral support from health professionals, while providers often need to address sources of frustration in treating difficult patients [37]. The use of advocacy and support groups may help bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…In diseases such as fibromyalgia, the psychosocial aspects of medical management become more essential, which may be due in part to providers’ lack of training and knowledge in effective therapies that address these challenges [36]. Indeed, these patients expect more moral support from health professionals, while providers often need to address sources of frustration in treating difficult patients [37]. The use of advocacy and support groups may help bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…We hoped to gain insights into the social construction of the illness from the patients' and professionals' perspectives (Briones-Vozmediano, Ronda-Pérez, & Vives-Cases, 2014; Briones-Vozmediano, Vives-Cases, Ronda-Pérez, & Gil-González, 2013). In the present study we focused on women´s accounts of daily events.…”
Section: Design and Participantsmentioning
confidence: 99%
“…This is a difficult condition to treat 18 and is a challenge both for patients who experience it and physicians who treat it. 19 Complementary therapies need to be explored. [20][21][22] Motivation and extent of practice A subset of those who completed the RCT went on to enter the extension trial (n = 20), which required further diligent qigong practice, and those who completed the extension trial (n = 13) reported prominent and sustained health benefits.…”
Section: Underlying Principles Of Qualitative Analysismentioning
confidence: 99%